Analisis Efisiensi pada Pra dan Pasca Initial Public Offering (IPO) Panin Dubai Syariah Bank - Dina Wening Ati Dianti; Irfan Syauqi Beik; Ascarya (AL-MUZARA'AH, 2020)
Panin Dubai Syariah Bank (PDSB) conducted an initial public offering (IPO) in January 2014 and was also registered as the first Islamic bank (IB) to conduct an IPO. With an IPO, PDSB is required to provide information disclosure and increase the company's competitive advantage. This study aims to determine 1) financial performance pre and post implementation of the PDSB IPO; 2) the efficiency of the pre and post implementation of the PDSB IPO compared to the IB BUKU 2. The study used a quantitative descriptive approach. The type of data used is secondary data in the form of annual report IB BUKU 2 2010-2017 and IB publication reports. Data were analyzed using the Data Envelopment Analysis (DEA) model to measure efficiency as a concept for evaluating PDSB performance. The results showed (1) CAR pre IPO better than post IPO. BOPO, NPF and FDR there are no significant differences between pre IPO and post IPO (2) PDSB efficiency scores in 2010-2017 are always more efficient when compared to IB BUKU 2. There are significant differences in the parameters of technical efficiency, pure technical efficiency, and scale efficiency on pre-IPO, while post-IPO significant differences only in the efficiency of technical efficiency and scale efficiency.